2017
DOI: 10.1177/0731684417710108
|View full text |Cite
|
Sign up to set email alerts
|

Elastic constants of tapered laminated woven jute/epoxy and woven aloe/epoxy composites under the influence of porosity

Abstract: Anisotropic nature of plant fiber and various plant fiber-correlated porosities are the major setbacks in evaluating the elastic constants of plant fiber-reinforced polymer composites theoretically. An attempt is made here to get rid of those setbacks and focuses toward the evaluation of accurate elastic constants of composites. In this work, mechanical characteristics such as tensile, flexure, and shear characteristics of woven jute/epoxy and woven aloe/epoxy composites are determined. The experimentally meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 46 publications
0
2
0
1
Order By: Relevance
“…Most importantly, they observed that the variability of lengthy natural fibre composites was considerably lower to that of one observed in previous investigations of single natural fibres. Suthenthiraveerappa and Gopalan [ 16 ] developed a combined model of laminate analogy and the Halphin–Tsai approach to evaluate the elastic constants of plant fibre fortified polymer composite (PFRP) in which the porosities concorded with plant fibre-fortified composites and the transversely isotropic material behaviour of plant fibre was considered. Kureemun et al [ 17 ] explored the performance enhancement of natural fibre-reinforced composites through the hybridization of carbon and flax fibres.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, they observed that the variability of lengthy natural fibre composites was considerably lower to that of one observed in previous investigations of single natural fibres. Suthenthiraveerappa and Gopalan [ 16 ] developed a combined model of laminate analogy and the Halphin–Tsai approach to evaluate the elastic constants of plant fibre fortified polymer composite (PFRP) in which the porosities concorded with plant fibre-fortified composites and the transversely isotropic material behaviour of plant fibre was considered. Kureemun et al [ 17 ] explored the performance enhancement of natural fibre-reinforced composites through the hybridization of carbon and flax fibres.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the buckling strength of the composite laminate was enhanced with the number of layers and it was also observed that the weaving style of a woven fabric affected the critical buckling load in which the basket type weaving model gave a better buckling strength. Suthenthiraveerappa and Gopalan [ 15 ] investigated the effect of porosity associated with natural, i.e., plant fiber, composites along with the transversely isotropic characteristics of plant fibers on the elastic constants of both jute and aloe fiber composites. A new methodology was also developed to estimate the elastic constants of uniform and taper polymer laminated composites reinforced with natural fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Karpiesiuk [126] em sua pesquisa sobre as propriedades do poliuretano para aplicação em pisos de alumínio obteve como resultado de ensaios de tração em adesivos de poliuretano o valor de 0,41. Já o coeficiente de Poisson da fibra de juta, com base nos trabalhos de Suthenthiraveerappa e Gopalan [127], foi estipulado um valor de 0,374. Dessa forma, é possivel obter um coeficiente de Poisson do compósito pela Regra das Misturas:…”
Section: Fibrasunclassified